Cost-Effectiveness Ratio (Cer) Pembangunan Bangunan Perlindungan Lereng - Komang Arya Utama; Dwianto Dwianto; Reny Khairina Damayanti (Jurnal Teknologi Berkelanjutan, 2025)
The construction of slope protection is an essential measure for maintaining soil stability and infrastructure integrity in landslide-prone areas. However, cost efficiency often becomes a point of contention due to variations in construction treatment types, geotechnical conditions, execution methods, and material selection. This study aims to analyze the cost-effectiveness of various slope reinforcement alternatives using the Cost-Effectiveness Ratio (CER) approach. The analysis was conducted on three critical slope locations along the national road sections of Gorontalo Province: Sta. 32+140, Sta. 34+340, and Sta. 5+540. Numerical simulations using Plaxis 8.2 software were employed to calculate the Safety Factor (SF) under both static and dynamic conditions. The results indicate that the implementation of slope protection measures increased the SF values by 30–73% (static) and 3–24% (dynamic). CER values demonstrated efficiency variations ranging from 3.7% to 54.68%, with the combination of retaining walls and bored piles yielding the highest cost-effectiveness. This study emphasizes the importance of design selection based on cost-effectiveness analysis in planning landslide mitigation for national roads to achieve effective and efficient designs.